Chemically modified tetracyclines: The novel host modulating agents - Devulapalli Narasimha Swamy; Sahitya Sanivarapu; Srinivas Moogla; Vasavi Kapalavai (Wolters Kluwer Medknow Publications, 2015)
Periodontal pathogens and destructive host responses are involved in the initiation and progression of periodontitis. The emergence of host response modulation as a treatment concept has resulted from our improved understanding of the pathogenesis of periodontal disease. A variety of drugs have been evaluated as host modulation agents (HMA), including Non Steroidal Anti Inflammatory Drugs (NSAIDS), bisphosphonates, tetracyclines, enamel matrix proteins and bone morphogenetic proteins. Chemically modified tetracyclines (CMTs) are one such group of drugs which have been viewed as potential host modulating agents by their anticollagenolytic property. The CMTs are designed to be more potent inhibitors of pro inflammatory mediators and can increase the levels of anti inflammatory mediators.